FRI0772-HPR Formal rheumatology training for general practitioners. (15th June 2017) - Khan, S; Mohammad, A; O'Rourke, KP; Sheeehy, C
Abstract : Background: Formal post graduate training in rheumatology is limited for primary care physicians or general practitioners. General practitioners (GPs) have extraordinary wide knowledge base, and deal with all age groups, from minor ailments to serious illnesses, thus it's not possible to expect them to have a strong hold of specialised conditions like inflammatory arthritis (IA) (2). General practitioners can be trained to manage these conditions in order to break the disconnect between the flow of knowledge and the burden of care in rheumatic conditions. Objectives: The Rheumatology department in Midlands Regional Hospital and University Hospital Waterford facilitates GPs teaching in rheumatology outpatients clinics. Every year six GP trainees are trained by consultant rheumatologist. Each trainee receives one on one education in managing rheumatologic conditions including joints and soft tissue injections. This survey was done to evaluate whether GP trainees benefited from it in diagnosing and treating rheumatologic diseases when compared to non rheumatology trainees. Methods: This is a cross sectional study of a convenience cohort. GP trainees who received rheumatology training as part of their hospital rotation were included as "cases", and compared to those who didn't have any formal rheumatology exposure during their training g as "control". The cases attended supervised rheumatology outpatients for one year, and. A questionnaire was emailed as well as distributed to the GP trainees, it included questions on trainees' ability and comfort level in diagnosing, assessing and managing inflammatory and non inflammatory conditions, along with joint and soft tissue injections. Results: There were 60 participants in the study, 30 cases and controls each. Majority (94%) didn't have formal rheumatology teaching in the medical school, but had rheumatology experience post graduation, 30 being GP trainee in rheumatology and 7 as senior house officers attached to rheumatology team. The GP trainees had an average of 7 months exposure to rheumatology. The GP trainees who attended the rheumatology clinics were confident in: examining joints, differentiating musculoskeletal/ mechanical from inflammatory conditions, educating patients and commencing them on DMARDs, interpreting serological tests (RF, CCP, ANA etc), managing osteoarthritis, tennis elbow, and soft tissue and intra-articular Knee and shoulder injections, as compared to the trainees who didn't have any formal rheumatology training (P<0.001). Conclusions: Rheumatology teaching for the GP trainees is certainly beneficial, and helps them in managing rheumatologic conditions in primary care settings. Acknowledgements: Dr Declan Brennan, General Practicioners Coordinator, Midlands, Tullamore. Disclosure of Interest: None declared